Pengaruh Lingkungan Keluarga, Teman Sebaya, dan Budaya Sekolah terhadap Karakter Siswa MTs Darul Ulum Waru Sidoarjo - Maria Widya Wanti; Laila Badriyah; Sholehuddin Sulaiman (Lembaga Yasin AlSys, 2026)
Although schools have systematically implemented various character education programs, character formation among students at the Madrasah Tsanawiyah level still shows behavioral variation, indicating that internal and external factors have not yet been fully integrated optimally. This study aims to analyze the influence of family environment, peers, and school culture on the character formation of students at MTs Darul Ulum Waru Sidoarjo, as well as to identify the variable that makes the greatest contribution. This study employed a quantitative approach with a survey design. The study population consisted of 834 students, with a sample of 288 eighth-grade students selected through purposive sampling. Data were collected using an eight-point Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted through instrument quality testing, classical assumption testing, and multiple linear regression analysis, while hypothesis testing used the t-test, F-test, and coefficient of determination (R²). The results showed that family environment, peers, and school culture had a partial and significant effect on student character. The Adjusted R Square value of 0.601 indicates that 60.1% of the variation in student character can be explained by these three variables, while 39.9% is influenced by other factors outside the research model. These findings also show that school culture is the most dominant variable influencing student character formation. Thus, student character formation requires family support, positive peer interaction, and consistency in school culture. This study affirms the importance of sustained collaboration between parents and schools in creating an environment that supports effective and sustainable character education.